FANOCRACY : Turning Fans into Customers and Customers into Fans - Scott, David Meerman; Scott, Reiko; Robbins, Tony ([New York, New York] : Portfolio/Penguin, 2020)
"Fandom isn't just for actors, athletes, musicians, and authors anymore. It can be rocket fuel for any business or nonprofit that chooses to focus on inspiring and nurturing true fans. The most powerful marketing force in the world isn't social media, email blasts, search ads, or even those 15 second commercials before a YouTube video. It's fandom. David Meerman Scott and his daughter Reiko are very different - one is a baby boomer business strategist, the other a millennial medical student. But both noticed that the kind of enthusiasm they once reserved for pleasures like the Grateful Dead (David) and Harry Potter (Reiko) now extends to all sorts of companies and organizations. So they teamed up to explore a big question: Why do some brands, even in supposedly boring categories like car insurance and enterprise software, attract not just customers but raving fans? The key is creating what they call a "fanocracy" - an organization that puts the needs and wishes of fans ahead of every other priority. It can be scary, at first, to focus on intangibles like community, generosity, and fun, rather than squeezing every penny from each interaction. But those who apply the strategies in Fanocracy are more likely to dominate their categories. And beyond the financial benefits, fanocracies spread more joy and inspiration to the world at large"--
Our story -- Strength through fandom -- The power of fan-centric business -- Get closer than usual -- Let go of your creations -- Give more than you have to -- Build identity to become more than the product -- Be smart about influencers -- Break down barriers -- Listen to rehumanize -- Tell the truth, especially when it hurts -- Develop employees who are fans -- A passionate life -- Share your fandom.
Includes index
Keywords: Relationship marketing; Customer relations -- Management; Consumer behavior